2002
DOI: 10.1086/342951
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis in Pregnancy in Tanzania. II. The Effectiveness of Antenatal Syphilis Screening and Single‐Dose Benzathine Penicillin Treatment for the Prevention of Adverse Pregnancy Outcomes

Abstract: Treatment for maternal syphilis with single-dose benzathine penicillin (2.4 million units intramuscularly) is being implemented in many parts of sub-Saharan Africa. To examine the effectiveness of this regimen, a prospective cohort of 1688 pregnant women was recruited in Tanzania. Birth outcomes were compared among women treated for high-titer (n=133; rapid plasma reagin [RPR] titer > or = 1:8 and Treponema pallidum hemagglutination assay [TPHA]/fluorescent treponemal antibody [FTA] positive) and low-titer (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 25 publications
2
113
0
3
Order By: Relevance
“…A previous study in Mwanza, Tanzania, published in 2002, showed that 51% of stillbirths and 24% of pre-term live births could be attributed to syphilis [19,20]. These adverse outcomes can be prevented with a single dose of penicillin given before 28 weeks of pregnancy [19], with this being one of the most cost-effective healthcare interventions available [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study in Mwanza, Tanzania, published in 2002, showed that 51% of stillbirths and 24% of pre-term live births could be attributed to syphilis [19,20]. These adverse outcomes can be prevented with a single dose of penicillin given before 28 weeks of pregnancy [19], with this being one of the most cost-effective healthcare interventions available [21].…”
Section: Discussionmentioning
confidence: 99%
“…These adverse outcomes can be prevented with a single dose of penicillin given before 28 weeks of pregnancy [19], with this being one of the most cost-effective healthcare interventions available [21]. Screening of pregnant women for syphilis is national policy in most countries; yet, in 2001, it was estimated that less than 40% of pregnant women were screened for syphilis in Sub-Saharan Africa [22].…”
Section: Discussionmentioning
confidence: 99%
“…21 This study allowed the concomitant measurement of the ims s portance and impact of other maternal factors in this population.…”
Section: Adverse Birth Outcomes In United Republic Of Tanzaniaimpact mentioning
confidence: 99%
“…21 In summary, a prospective cohort of 1688 women ats s tending an antenatal clinic (ANC) was recruited from the main ANC in Mwans s za city from 1997 to 2000 to examine the effectiveness of antenatal screening and treatment of syphilis. Women were screened at the ANC for syphilis by the rapid plasma reagin assay (RPR).…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation